2021
DOI: 10.3389/fneur.2021.683048
|View full text |Cite
|
Sign up to set email alerts
|

Update in Autoimmune Movement Disorders: Newly Described Antigen Targets in Autoimmune and Paraneoplastic Cerebellar Ataxia

Abstract: Movement disorders are a common feature of many antibody-associated neurological disorders. In fact, cerebellar ataxia is one of the most common manifestations of autoimmune neurological diseases. Some of the first autoantibodies identified against antigen targets include anti-neuronal nuclear antibody type 1 (ANNA-1 or anti-Hu) and Purkinje cell cytoplasmic antibody (PCA-1) also known as anti-Yo have been identified in paraneoplastic cerebellar degeneration. Historically these antibodies have been associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 45 publications
0
13
0
2
Order By: Relevance
“…Our novel finding of neurochondrin autoantibodies in conjunction with AD dementia seems surprising at first glance, as neurochondrin autoimmunity has only been reported so far in association with vestibulocerebellar syndromes ( 1 , 7 9 ) and movement disorders ( 2 , 10 ) and only rarely with cognitive dysfunction in children ( 3 ). Neurochondrin is required during embryogenesis, as embryos lacking the neurochondrin gene die early during their embryogenesis ( 11 ).…”
Section: Discussionmentioning
confidence: 80%
“…Our novel finding of neurochondrin autoantibodies in conjunction with AD dementia seems surprising at first glance, as neurochondrin autoimmunity has only been reported so far in association with vestibulocerebellar syndromes ( 1 , 7 9 ) and movement disorders ( 2 , 10 ) and only rarely with cognitive dysfunction in children ( 3 ). Neurochondrin is required during embryogenesis, as embryos lacking the neurochondrin gene die early during their embryogenesis ( 11 ).…”
Section: Discussionmentioning
confidence: 80%
“…Cerebellar Purkinje cells highly express a scaffold molecule Homer-3, and its antibodies also induce cerebellitis and ataxia [157,158]. Furthermore, antibodies against glutamic acid decarboxylase (GAD), GluD2, Caspr2, mGluR2, AP3B2, ITPR1, and NIF are also suggested to link with immune-mediated ataxia, although the mechanism remains poorly understood [159][160][161][162]. Several environmental factors, including exposure to toxic chemicals, gluten-containing diets, and diseases, such as cancer, affect the formation of autoantibodies [163].…”
Section: Cerebellar Atrophy and Host Autoimmunitymentioning
confidence: 99%
“…Recent studies have shown that selective antibodies against molecules of the mGluR1 pathway are often present in patients with Autoimmune Cerebellar Ataxia. Importantly, many of these antigens are also associated with the pathogenesis of spinocerebellar ataxias [ 113 , 114 , 115 ]. This clinical evidence suggests that the mGluR1 signaling pathway may be a common pathophysiological mechanism not only in SCAs but also in other conditions with signs of cerebellar ataxia.…”
Section: Shared Mglur1-pkcγ Signaling Pathway In Scasmentioning
confidence: 99%